The Author Was Not an Author: The Copyright Interests of Photographic Subjects from Wilde to Garcia* - Subotnik, Eva. E. (The Columbia Journal of Law & the Arts, 2016)
Toward the end of his dissent in the Ninth Circuit’s en banc opinion in Garcia v. Google, Judge Alex Kozinski remarked that “[w]hen modern works, such as films or plays, are produced, contributors will often create separate, copyrightable works as part of the process.”Judge Kozinski’s characterization of plays (or even films) as “modern works” opens the door to an examination of that claim with respect to another genre of “modern work[]”: the photograph. As I will discuss, Judge Kozinski’s claim has not been true of the allocation of rights within that medium. It is therefore surprising that the majority opinion in Garcia did not cite the Supreme Court’s opinion in Burrow-Giles Lithographic Co. v. Sarony. For, as the Ninth Circuit itself had recognized on an earlier occasion, that famous case would seem to be a logical and important precedent for the proposition that, as among multiple potential contributors to an overarching fixed visual work, there is a legally relevant hierarchy. Relatedly, Burrow-Giles would seem to stand for the principle that, unlike the differentiable layers of an onion, in many instances there simply are no micro-authored subparts of the whole to which copyright attaches.